2014
DOI: 10.1007/s13364-014-0209-6
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the red fox (Vulpes vulpes) in the UK

Abstract: The red fox (Vulpes vulpes) is common and widely distributed within the UK. It is a carrier or potential carrier of numerous zoonotic diseases. Despite this, there are no published reports on the population genetics of foxes in Britain. In this study, we aim to provide an insight into recent historical movement of foxes within Britain, as well as a current assessment of the genetic diversity and gene flow within British populations. We used 14 microsatellite markers to analyse 501 red fox samples originating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…This pattern has variously been attributed to anthropogenic introductions associated with historical cultural connections (Mascheretti et al 2003;O'Meara et al 2012), population expansion causing a replacement of intervening populations (O'Meara et al 2012), or a population bottleneck causing a loss of connecting haplotypes from intervening populations (Jordan et al 2012). Given the history of fox translocation globally (Long 2003;Statham et al 2012), a potential population size reduction in Britain due to hunting (Atterby et al 2015), and the greater diversity of haplotypes found in Ireland than in Britain, any one of these scenarios could explain the patterns seen. Additionally, increased sampling in Britain may uncover the same or similar Spanish type haplotypes, thus indicating genetic continuity between British and Irish red foxes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern has variously been attributed to anthropogenic introductions associated with historical cultural connections (Mascheretti et al 2003;O'Meara et al 2012), population expansion causing a replacement of intervening populations (O'Meara et al 2012), or a population bottleneck causing a loss of connecting haplotypes from intervening populations (Jordan et al 2012). Given the history of fox translocation globally (Long 2003;Statham et al 2012), a potential population size reduction in Britain due to hunting (Atterby et al 2015), and the greater diversity of haplotypes found in Ireland than in Britain, any one of these scenarios could explain the patterns seen. Additionally, increased sampling in Britain may uncover the same or similar Spanish type haplotypes, thus indicating genetic continuity between British and Irish red foxes.…”
Section: Discussionmentioning
confidence: 99%
“…This subspecies designation includes several distinct populations resolved in our study, including those in Italy, and on the islands of Ireland and Britain, which have been physically and genetically isolated since the late Pleistocene/early Holocene. Despite translocations into Britain during historical times (Long 2003;Atterby et al 2015), this population has maintained a distinct genetic character. Taken together, these data indicate that both Irish and British red foxes should be considered evolutionarily distinct units within the red fox.…”
Section: Comparison Of Genetic Subdivision With Recognized Subspeciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxes are present throughout all the country in a different geographical regions and habitats. The significant genetic differences between fox populations dependent on the place of occurrence have been found in many studies (Atterby et al 2015, Edwards et al 2012, Mullins et al2014, Oishi et al 2011, Wandeler et al 2003.…”
Section: Introductionmentioning
confidence: 86%
“…Apart from intensive selective breeding carried out on fur farms the second important factor which may be responsible for significant morphological differences between wild and farm foxes is the origin of compared populations (Statham et al 2011). This may lead to different gene pools and genetic structures of red fox populations inhabiting different regions of the northern hemisphere (Mullins et al 2014;Atterby et al 2015). Genetic distinctiveness of populations of the same species may produce favourable conditions for divergence between populations and the evolution of a new species (e.g., Vulpes fulva; Statham et al 2014).…”
Section: Introductionmentioning
confidence: 99%